Organizational Culture and Motivation Influence on Nurse Performance with Organizational Commitment as a Intervening Variable at Satya Hospital - Utama Satyanegara; Supriyantoro Supriyantoro; Rian Adi Pamungkas (Jurnal Health Sains, 2023)
Organizations have specific goals, structures and interrelated goals and rely on human communication to coordinate organizational activities. Therefore, the organization expects employees to excel and create conducive situations and conditions so that employees do not experience boredom, boredom and laziness at work, leading to decreased performance. Human resources are essential for hospitals. Therefore, human resources must perform competently to achieve the hospital's vision and mission. The purpose of this study was to analyze the influence of organizational culture and motivation on the performance of nurses with organizational commitment as an intervening variable at Satya Negara Hospital, Sunter, North Jakarta. The sample used was 115 nurses. This research uses explanatory causality quantitative analysis with AMOS SEM quantitative method. The results showed that there was a significant influence of organizational culture and motivation on the performance of nurses through organizational commitment as an Intervening variable; There is no significant effect between organizational culture on organizational commitment; There is a positive and significant influence between motivation and organizational commitment; There is a positive and significant influence between organizational culture on nurse performance; There is a positive and significant effect between motivation on nurse performance; There is a significant influence between organizational commitment to the performance of nurses at the Satya Negara Hospital, Sunter, North Jakarta. It was concluded that the H1, H3, H4, H5 and H6 hypotheses were accepted, while the H2 hypothesis, namely the influence of organizational culture on organizational commitment, was not proven to be significant. The research impliimplies optimal nursing service can be achieved if nurses perform optimal.